Influence of mechanical activation on SrTiO3 mixture with Fe2O3 as aditive - Živojinović Jelena A.; Peleš-Tadić Adriana P.; Kosanović Darko A.; Filipović Suzana Ž.; Stanković Ana V.; Obradović Nina N. (Tehnika, 2023)
The authors investigated the influence of mechanical activation on the structure of SrTiO3 mixture with 6 wt.% Fe2O3. Powders were mechanically activated in a planetary ball mill with WC balls in time intervals from 0 to 120 minutes. XRD method was used for the identification of phase structure, while SEM and PSA were employed for monitoring of changes in morphology and particle size distribution. Structural changes were followed by Raman spectroscopy, and band gap values were calculated as well. The purpose of mechanical activation is lowering the temperature and time of sintering in the process of obtaining the final product.